Painéis aglomerados com resíduo de Pinus caribaea var. caribaea com adesivo bicomponente sustentável - Souza, Matheus Viana De [UNESP]; Silva, Sérgio Augusto Mello Da [UNESP]; Cazella, Pedro Henrique Da Silva [UNESP]; Rodrigues, Felipe Reis [UNESP]; Carneiro, Tainah Eduarda Boian [UNESP]; Pinto, Edna Moura; Martins, Aline Redondo [UNESP]; Aouada, Márcia Regina De Moura [UNESP]; Christoforo, André Luis (Associação Nacional de Tecnologia do Ambiente Construído - ANTAC, 2023)
This research aimed to produce and evaluate particleboard with pinus waste using two production methodologies. One applied to homogeneous panels (single layer) and another to heterogeneous panels (three layers). The panels were produced with an initial density of 0.550 g/cm³, with 10% polyurethane resin derived from castor oil (PUR) for the homogeneous panels and 12% for the heterogeneous ones. The pressing parameters were 5 MPa, with a temperature of 100 ºC and 10 min of pressing, with an interval of 30 s. The tests performed according to NBR 14810-2 (ABNT, 2018) standard. As a result, it was observed that the reorganization of the particles of the heterogeneous panels added to the increase of the adhesive were factors that improved the final properties of the panels, which are classified to be used as decoration objects and in the furniture industry, not obtaining classification of homogeneous panels.

Esta pesquisa teve como objetivo produzir e avaliar painéis aglomerados com resíduo de pinus medianteuma metodologia de produçãoaplicada para painéis homogêneos e outra para heterogêneos. Os painéis homogêneos e heterogêneos foram produzidos com densidade inicial de 0,550 g/cm³ e com 10% e 12% de resina de poliuretano derivado do óleo de mamona (PUR) respectivamente. Os parâmetros de prensagem foram de 5 MPa, com temperatura de 100 ºC e 10 min de prensagem, com um intervalo de 30 s. Os ensaios realizados seguiram a normativa NBR 14810-2 (ABNT, 2018). Observou-se que a reorganização das partículas dos painéis heterogêneos somada ao aumento do adesivo foram fatores que melhoraram as propriedades finais desses painéis, classificados para ser utilizados como objetos de decoração e na indústria moveleira, enquanto os painéis homogêneos não obtiveram classificação.
Particleboard with residue of Pinus caribaea var. caribaea with sustainable bi-component adhesive
Keywords: Particleboards; Wood waste; Polyurethane derived from castor oil; Painéis aglomerados; Resíduo madeireiro; Poliuretano derivado do óleo de mamona